Pengaruh Motivasi, Loyalitas dan Disiplin Kerja terhadap Kinerja Karyawan PT. Kara Santan - Kholilah; Efrina Masdaini; Qisoshul Haqie (Politeknik Negeri Sriwijaya, 2024)
This study aims to analyse the effect of motivation, loyalty, and work discipline on employee performance of PT Kara Santan Pertama. This research uses a quantitative approach with data collection methods through questionnaires filled out by 53 respondents from a total of 65 permanent employees. The data analysis technique was carried out using multiple linear regression with the hypothesis of f test, t test and coefficient of determination. The results showed that motivation, loyalty, and work discipline simultaneously had a significant effect on employee performance. Partially, each independent variable also shows a significant positive effect on performance. Work discipline has the most dominant influence compared to other variables. This study concludes that increasing motivation, loyalty, and work discipline can significantly improve the performance of PT Kara Santan Pertama employees.